PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA NEGERI 3 PADANG TAHUN PELAJARAN 2012/2013 - Putra, Wahyudi; Rismen, Sefna; Husna, Husna (Pendidikan Matematika, 2013)
The background of this research is the studentsâ comprehension of mathematic concept in XI IPA SMA Negeri 3 Padang school year 2012/2013.The problem can be solved by applying cooperative learning strategy type Student Team Achievement Division (STAD) in mathematic learning to increase their comprehension of mathematic concept. The aim of the research is to know that studentsâ comprehension of mathematic concept which is applied cooperative learning strategy type STAD much better than studentsâ comprehension of mathematic concept which is applied by conventional learning.This is an experiment research with all of students XI IPA in SMA Negeri 3 Padang as the population. From that population, XI IPA is chosen as experimental class and XI IPA 5 as control class. Then, final test is used to measure studentsâ comprehension of mathematic concept which has the indicators of comprehension of mathematic concept which has reliability of instrument, r11 = 0,81.One way Mann-Whitney test is used to test the hypothetic. Based on measurement, Z = -0, 02 was less from Z0,05 = 1,65. It is indicate the hypothetical of research is refused. So, it can be concluded that studentsâ comprehension of mathematic concept which is applied cooperative learning strategy type STAD is the same with studentsâ comprehension of mathematic concept which is applied conventional learning in XI IPA SMA Negeri 3 Padang school year 2012/2013.